The use of large denomination banknotes in Switzerland - Katrin Assenmacher; Franz Seitz; Jörn Tenhofen (Deutsche Bundesbank, 2017)
We study the demand for Swiss banknotes over the period from 1956 to 2015 and present stylized facts on different banknote denominations since the inception of the Swiss National Bank (SNB) in 1907. Employing the so-called seasonal method, we focus on the demand for banknotes used as a store of value (“hoarding”), which can be expected to be particularly relevant for Switzerland against the backdrop of its status as a safe-haven country, its currently and historically low level of interest rates, and a banknote denomination with the largest value among advanced countries. Due to the pronounced seasonal pattern of CHF 1000 banknotes, which might not be related to transactions, we cannot rely on seasonal ranges including the December peak. Instead, we employ other peak dates as well as a method to correct for the excess seasonality, using institutional features of the tax system. The latter approach is not sufficient to eliminate the excess seasonality and thus does not lead to plausible estimates for the hoarding share of CHF 1000 banknotes. Employing other peak dates, however, indicates that since the turn of the millennium the share of CHF 1000 banknotes that is hoarded increased steadily from around 30% in the mid-1990s to over 70% in recent years.
Keywords: E41; E52; E58; 330; currency in circulation; banknotes; hoarding